Konsep Metode Pendidikan dalam Perspektif Al-Quran: Kajian Analisis tentang Pendidikan Islam - Firdaus Farazuha; Muhammad Miftah Nurul Amin; Fairus Sakila (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Education holds an extremely important position in Islam, with the Quran and Hadith serving as the primary foundation for developing teaching methodologies. This journal aims to examine the concept of educational methods contained in these two sources. Through a qualitative approach employing thematic interpretation (maudhu'i) and hadith verification (takhrij), this research seeks to explore educational methods understood as a set of systematic approaches and techniques for instilling values to realize the perfect human being (insan kamil). This study successfully identifies various methods, including: 1) lecture method, 2) discussion, Q&A, or dialogue method, 3) awareness-raising method, 4) reward and punishment method, and 5) exemplary model method. These methods possess distinctive characteristics of being divine, humanistic, adaptive, gradual, and focused on moral transformation. Meanwhile, aspects requiring greater attention lie in their implementation, which demands deep contextual understanding and educator innovation to contextualize them with contemporary realities. The conclusion of this research confirms that educational methods in the Quran and Hadith present an integrative educational perspective rich in wisdom.